Faktor yang Mempengaruhi Soft Skill Siswa SMK Negeri 2 Blitar Dalam Menghadapi Dunia Kerja di Era Revolusi Industri 4.0 - Sulastri Sulastri; Annisa Herawati (Jurusan Ekonomi Pembangunan Fakultas Ekonomi Universitas Negeri Malang, 2021)
This study aims to provide empirical evidence on what factors impact the development of soft skills in vocational school students who will become future national economic mobilizers. The focus of this research was to determine whether there is a distinction between the soft skills profile of vocational school graduates and the requirements of the workplace in the world. The variables consist of learning processes (X1), industrial training (X2), and student’s soft skills (Y).This research uses a quantitative approach. The population of this study is 130 students of XII SMK Negeri 2 Blitar from Accounting and Financial Institution expertise program. Sampling is done by proportional random sampling technique. Data collection is done by using questionnaires. Technical data analysis uses multiple linear analysis with the help of SPSS software. The results showed that: the learning process has a significant effect on students' soft skills, showing a significance value of 0.00 below ρ value of 0.05; and field practice had no significant effect on the student's soft skills, indicating a significance value of 0.357 above ρ value of 0.05. DOI: https://dx.doi.org/10.17977/UM014v21i22021p129